Explosive ordinance disposal multiservice procedures for EOD in a Joint Environment
This manual identifies standard tactics, techniques, and procedures among the services for planning, integrating, and executing EOD operations. Subjects covered in great detail are: EOD within the Department of Defense; EOD in a Joint Environment; Army EOD Operations; Marine Corps EOD Operations; Navy EOD Operations; Air Force EOD Operations; Multiservice EOD Capabilities Matrix; EOD Recurring Support Operations